Potential Effect of Medical Insurance on Medicare: Evidence from China - Yongqiu WU; Yi HUANG; Jintao LU (Tehran University of Medical Sciences, 2016)
Background: With the increased range of medical insurance coverage in China, the proportion of medical expenditure shouldered by individuals is declining. The problem is the rapidly growing scale of medical expenditures challenges the sustainability of medical insurance funds. Methods: This study used the Heckman selection model, survival analysis, and ordered probit model to evaluate the effect of medical insurance on the expenditures in outpatient and inpatient health care, survival time, and improvement of self-rated health of test subjects, respectively. Results: Medical insurance exerts a differential effect on the expenditures in outpatient and inpatient health care. On average, the expenditures in outpatient and inpatient health care of test subjects participating in premium health insurance plans increased by 38.6% and 72.6%, respectively. Participation in medical insurance plans exhibits no significant correlation with the survival time of test subjects, but their self-rated health shows a significant correlation (P < 0.01). Conclusion: Although medical insurance does not significantly reduce mortality or prolong the survival time of test subjects, it improves their health status. This study suggests that the Chinese government should eliminate deductible medical insurance payments and utilize medical resources on minor ailment treatment and disease prevention to improve the health status of people.